Attractors in Dark Energy Models with Born-Infeld Scalar Field - Ronaldo Carlotto Batista (Brazilian Journal of Physics, 2005)
We derive, in the large scale limit, analytical solutions for a dark energy model described by the Born-Infeldfield plus a perfect fluid, both for homogeneous background and first order perturbations. These analyticalresults are compared with numerical solutions in a model with radiation, pressureless matter and the field. Weinvestigate the non-adiabatic perturbed pressure associated with this attractor and whether it corresponds toisocurvature contribution.